STRATEGI MARKETING POLITIK AZHARI NARDI DAN YOHANES LINDUNG MANGATAS SIMBOLON DARI P-DIP DALAM MEMENANGKAN KURSI DPRD KABUPATEN KAMPAR PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2024 - Pradana, Dimas Ari; ,, Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to determine how the use of political marketing strategies carried out by Azhari and Yohanes in facing the Kampar Regency Election in 2024. So that the votes increase, This study uses a qualitative research method with a descriptive approach. Data collection techniques are carried out by in-depth interviews, literature studies, and documentation. Analyzed using data reduction, data presentation and drawing conclusions. The results of this study indicate that the political marketing strategy carried out by Azhari and Yohanes is in line with the Adnan Nursal theory approach model, namely 3P which is structured and directed properly.This study aims to understand the influence of the implementation of the elimination of the motor vehicle testing levy on its services at the Agam Regency Transportation Office. This research was conducted with a qualitative descriptive approach. By using the main theory, namely the theory of policy implementation by Charles O Jones with 3 indicators, namely Organization, Interpretation and Application of policies. he political marketing strategies used by Azhari and Yohanes include. First, pull marketing, namely through Instagram, Facebook, and Tiktok. Second, push marketing by holding meetings with the community. Third, pass marketing by inviting local figures to support Azhari and Yohanes. The results of the study show that community segmentation, technological advances and local figures, internal aspects, external aspects are supporting factors in the P-DIP Party's marketing strategy process. There are also several obstacles in the political marketing process carried out by the P-DIP Party, including the lack of a mass base and the lack of networks with other major parties. Keywords: Pull Marketing, Push Marketing, Pass Marketing, Party, Political Marketing, Improvement, P-DIP